Pelatihan Digital Marketing Syariah sebagai Pendukung Pertumbuhan UMKM di Geprek Cila - Desriani, Wiwit; Yulia, Sandre; Zaldi, Farhan; Yustati, Herlina; Harpepen, Andi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Geprek Cila through the use of digital marketing. The reason for choosing this topic is based on the great potential of MSMEs in driving the local economy and the challenges faced in adapting to the digital era. This research activity uses intensive training and mentoring methods regarding digital marketing strategies, utilization of social media, promotional content creation, and simple analysis of the effectiveness of online marketing. The results of this study indicate an increase in understanding and skills of MSME actors in implementing digital marketing to expand market reach, increase interaction with consumers, and ultimately it is expected to increase their business income. In addition, this activity also builds awareness of the importance of technology adaptation in the sustainability of MSME businesses in the digital era.